2020
DOI: 10.1155/2020/8948249
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Perimembranous Ventricular Septal Defects Using Different Generations of Amplatzer Devices: Multicenter Experience

Abstract: Objectives. To demonstrate safety and efficacy of using different generations of softer Amplatzer ™ devices for ventricular septal defect (VSD) closure to avoid serious complications at follow-up. Background. Transcatheter closure of perimembranous ventricular septal defects (PmVSD) is a well-established procedure; however, it is associated with unacceptable incidence of complete heart block. Great advantages have been achieved by using softer devices for VSD transcatheter closure. e first and second generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
(33 reference statements)
2
21
0
3
Order By: Relevance
“…So far, the underlying mechanism of arrhythmias after transcatheter pmVSD closure is still unclear. The risk factors may include age, weight, operation duration time, operation technique, anatomy location of the pmVSD, size of the occluder, morphological characteristics of the occluder, and so on, but the conclusions about risk factor were different in various researches [ 5 , 12 , 15 , 39 ]. In this study, younger patients with large size occluder, asymmetrical concentric or eccentric occluder, and undergoing the operation on an early time might easily get arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the underlying mechanism of arrhythmias after transcatheter pmVSD closure is still unclear. The risk factors may include age, weight, operation duration time, operation technique, anatomy location of the pmVSD, size of the occluder, morphological characteristics of the occluder, and so on, but the conclusions about risk factor were different in various researches [ 5 , 12 , 15 , 39 ]. In this study, younger patients with large size occluder, asymmetrical concentric or eccentric occluder, and undergoing the operation on an early time might easily get arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatments of pmVSD mainly include interventional occluder closure and surgical repair. Compared with the surgical repair, up to now, the interventional treatments are still controversial [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13–16 A retrospective study involving 119 patients found that Amplatzer vascular plug and Amplatzer duct occluder I and II seem to be safe for the closure of VSD and they can be used off-label with good mid-term results. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Hasta la fecha hemos realizado un total de 36 procedimientos con buenos resultados, con un índice de cierre del 100% y, lo más importante, libre de complicaciones. Recientemente publicamos en un estudio multicéntrico la experiencia de nuestro país y del grupo cardiovascular de Egipto en los últimos nueve años en donde se reportaron un total de 119 pacientes con una mediana de edad de 5 años y peso de 18 kg que fueron llevados a cierre de comunicación interventricular perimembranosa utilizando dispositivos ADO de primera y segunda generación, así como dispositivos AVP II, en donde se reportó un índice de cierre del 98.3% y no se reportó ningún caso de bloqueo atrioventricular a un seguimiento a 36 ± 25.7 meses 17 . También reportamos el cierre de un defecto ventrículo-atrial (Gerbode) con un dispositivo AVP II  en un paciente de sexo masculino de 10 años de edad con antecedente de corrección de conexión anómala parcial de venas pulmonares derechas al atrio derecho 18 .…”
Section: C B Funclassified